Preconcentration of Synthetic Phenolic Antioxidants in Instant Noodle Samples by Alcohol-Based Vortext-Assisted Liquid-Liquid Microextraction and Determination by High-Performance Liquid Chromatography - Liu, Chang; Liu, Ye; Jiao, Yang; Bi, Li; Yang, Yaling (Asian Journal of Chemistry, 2014)
In this work, a novel method termed as vortext-assisted liquid-liquid microextraction (VALLME) combining high performance liquid chromatography with diode array detection (HPLC-DAD) was developed for the determination of synthetic phenolic antioxidants in instant noodle samples. The isobutanol was used as extractant and the vortex-mix was utilized to reduce extraction time and improve extraction efficiency. Under the function of vortex-mix, it is favorable for the mass transfer of the analytes from the aqueous sample to the extraction solvent. Parameters affecting the extraction efficiency were systematically investigated. Under the optimal conditions, the spiked recoveries for analytes were in the range of 89.5-110.5 % and the limits of detection (LOD) for all target analytes were in range of 1.5 to 6.4 μg L-1 (S/N = 3). The experimental results indicated that the proposed procedure was successfully applied to the determination of synthetic phenolic antioxidants in instant noodle samples.